(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Left ventricular function, volumes and regional wall motion provide valuable diagnostic information and are of long-term prognostic importance in patients with dilated cardiomyopathy (DCM). This study was designed to assess the agreement between the 2D-echocardiography and gated single-photon emission tomography (SPECT) for evaluation of these parameters in patients with DCM. Patients and methods: Gated SPECT and 2D-echocardiography were performed in 60 patients having DCM. Gated SPECT data, including left ventricular volumes and left ventricular ejection fraction (LVEF), were processed using an automated algorithm. Standard technique was used for 2D-echocardiography. Regional wall motion was evaluated using both modalities and was scored by two independent observers using a 4-point scoring system for 5 specific walls. Results: The overall agreement between the two imaging modalities for the assessment of regional wall motion was 95% (286/300 walls). With gated SPECT left ventricular ejection fraction (LVEF), end-diastolic volume (EDV), and end-systolic volume (ESV) were 27.38±6.71%, 214.73±75.35 ml, and 158.33±63.22 ml, respectively, and 31.25±5.09%, 185.05±55.63 ml, and 123.47±46.00 ml, respectively, with echocardiography. The correlation between gated SPECT and 2D-echocardiography was moderate (r = 0.59, P<0.001) for the assessment of LVEF. The correlation for EDV and ESV were also moderate, but with wider limits of agreement (r = 0.62, P<0.001 and r = 0.65, P<0.001, respectively) and significantly higher values were obtained with gated SPECT (P<0.001). For EDV, Bland-Altman measurements agreement analysis between the two methods demonstrated good agreement with finding of bias 29.68 and showed large limits of agreement, 95% upper and lower limit of agreement in 148.82 to -89.45 ml interval. For ESV, Bland-Altman measurements agreement analysis between them demonstrated good agreement with finding of bias 33.3 and showed large limits of agreement, 95% upper and lower limit of agreement in 130.12 to -63.52 interval. For LVEF, Bland-Altman measurements agreement analysis between them demonstrated good agreement with finding of bias 3.9 and 95% upper and lower limit of agreement in +14.8% to -7.0% interval. Conclusion: Gated SPECT and 2D-echocardiography correlate well and by Bland- Altman agreement analysis they exhibit good agreement with large limits for the assessment of LV function and LV volumes. Like 2D-echocardiography, gated SPECT provides reliable information about LV function and dimension with the additional advantage of perfusion data. Bangladesh J. Nuclear Med. 24(1&2): 28-35, 2021